Corundum Molds for Investment Casting from Refractory Alloys and Metals - P. A. Storozhenko; G. I. Shcherbakova; D. V. Sidorov; M. S. Varfolomeev; A. S. Murkina (Advances in Materials Science and Engineering)
Production procedure, physical-chemical, and performance properties of ALUMOX silica-free binder used for the production of high-heat-resistant corundum shell molds by consumable patterns employed in the production of critical molds from superalloyed reactive metals and alloys are described. ALUMOX usage allows obtaining casts from reactive metals and alloys with surface roughness up to 𝑅𝑧<10 𝜇m (basic casts—𝑅𝑧>60 𝜇m), which, in its turn, increases fatigue parameters of the material (endurance, durability).